1977
DOI: 10.1136/adc.52.7.545
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in blood pressure during exchange transfusion.

Abstract: SUMMARY Blood pressure changes as a function of the rates of blood withdrawal and infusion were determined during exchange blood transfusion in 2 preterm newborn infants. 10 ml blood withdrawal and infusion completed within 3 minutes resulted in reversible changes in aortic pressure, whereas the same procedure completed within 45 to 60 seconds resulted in a progressive fall in the systolic pressure and in narrowing of the pulse pressure. In one of the cases this was associated with respiratory arrest. An excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…In this study, we confirmed earlier findings of blood pressure changes during exchange transfusion [1,2]. Recently, we studied cerebral blood flow and electrical brain activity during exchange transfusions also using the 'pushpull' method in the newborn lamb.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, we confirmed earlier findings of blood pressure changes during exchange transfusion [1,2]. Recently, we studied cerebral blood flow and electrical brain activity during exchange transfusions also using the 'pushpull' method in the newborn lamb.…”
Section: Discussionsupporting
confidence: 76%
“…During exchange transfusions with the 'pull-push' method, acute changes in circulating blood volume lead to changes in arterial blood pressure and intracranial pressure [1][2][3]. We observed changes in cerebral blood volume, as determined with near infrared spectroscopy, during exchange transfusions in newborn infants [4].…”
Section: Introductionmentioning
confidence: 78%
“…Multivariate analysis was also performed to determine the simultaneous association of changes in HR, MABP, Q car , and exchange cycle duration with changes in ECBA. The following model was used: multivariate analysis of variance changes in Q car and ECBA, respectively, by exchange transfusion [1,10] with (covariates) [3]. A p value !…”
Section: Discussionmentioning
confidence: 99%
“…During an exchange transfusion by the conventional push-pull technique, approximately 10% of the circulating blood volume of the infant is withdrawn and donor blood is infused in a relatively brief period. These acute changes in circulating blood volume lead to changes in arterial blood pressure [1], intracranial pressure [2], and ce-rebral blood volume as determined by us in (near) term babies with near infrared spectroscopy (NIRS) [3]. Infants who had undergone exchange transfusions in their (early) neonatal period appeared to be at risk for later failure in school [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover this slow rate of exchange transfusion corresponds to the one (of 5 ml/kg per 3 min) recommended by Aranda and Sweet (1977) as producing only minimal, rapid, reversible changes in the blood pressure. The observed lower angiotensin I levels in the jaundiced infants with G-6-PD were probably due to the young age (24 days median) of the infants and not to increased haemolysis.…”
mentioning
confidence: 87%